Micronutrient Supplementation and Deworming in Children with Geohelminth Infections - Rajagopal, Selvi; Hotez, Peter J.; Bundy, Donald A. P. (Public Library of Science, 2015)
Soil-transmitted helminth (also known as “geohelminth”) infections are among the most common chronic infections worldwide. The World Health Organization (WHO) estimates that almost 900 million children require treatment (also known as deworming) for geohelminth infection, while the 2010 Global Burden of Disease Study estimates that more than 5.2 million disability-adjusted life years (DALYs) are attributable to geohelminth infection. In 2001, the World Health Assembly resolved to treat 75% of children at risk for morbidity from these geohelminths by 2010. However, WHO reported that by 2010 only approximately one-third of all children at risk had achieved access to mass drug administration (MDA). Treating the remaining two-thirds by 2020 is the target of the 2012 London Declaration for Neglected Tropical Diseases.